THE CONSERVATION OF MODERN IN CANADA - France Vanlaethem; James Ashby; Robert Lemon; Steven Mannhell (Docomomo Journal, 2022)
THE PUBLICATION of this issue of the Docomomo Journal, ahead of the lcomos 16th General Assembly and International Scientific Symposium which will be taking place in Quebec in late September 2008, presents an opportunity for taking stock of the modern movement's conservation in Canada…